Introgression of peanut smut resistance from landraces to elite peanut cultivars (Arachis hypogaea L.) - Bressano, Marina (2019)
Fil: Bressano, Marina. Universidad Nacional de Córdoba. Facultad de Ciencias Agropecuarias; Argentina.